Efektivitas Media Pembelajaran Intelligence Stick untuk Peningkatan Pembelajaran Operasi Pengurangan Deret Kebawah pada Anak Tunadaksa - Benzani, Cesa Almaidah; Nurhastuti, Nurhastuti (Jurnal Penelitian Pendidikan Khusus, 2022)
The research was motivated by the problem of a fourth grade quadriplegic child who did not understand the operation of reducing the series down borrowing system. Intelligence Stick makes it easy for children to perform operations to reduce the series down borrowing system for children with disabilities. The purpose of this study is to improve learning operations for subtracting the downward series of the borrowing system for class IV SLB Hikmah Miftahul Jannah Padang. Baseline condition A1 obtained results of 0%, 0%, 0%, 0%. Condition B obtained results of 35%, 55%, 60%, 60%, 65%, 75%, 80%, 80%. Baseline condition A2 obtained results of 80%, 85%, 90%, 90%. The results of the data analysis showed that the ability of the downward series reduction operation with the borrowing system increased after using the Intelligence Stick media on children with disabilities.